Diversifikasi Produk Berbahan Dasar Ikan Patin Untuk Meningkatkan Pendapatan Masyarakat Di Desa Bincau Kecamatan Martapura Kabupaten Banjar - Emmy Lilimantik; Nurma Sari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
Striped catfish is one of the leading sectors in aquaculture in Banjar Regency, it is stated in the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number. KEP.32/MEN/2010 and the Decree of the Banjar Regency Number. 241 of 2008 about the Stipulation of Striped Catfish Cultivation Fisheries Areas. Until this time, striped catfish production is mostly sold in fresh form in traditional markets from South Kalimantan to Central Kalimantan and East Kalimantan. Whereas striped catfish can be processed into various varied and productive forms because it has a rich taste, colored meat with a chewy texture, highly nutritious and affordable prices. To increase the utilization of striped catfish, it is necessary to have processed products in order to increase the income of the surrounding community. The Community Partnership Program activity aims to transfer community technology through training in processing various foods made from striped catfish. The method consists of (a) counseling and (b) practical demonstration which aims to provide knowledge and skills to the target audience, which are the communities around the striped catfish minapolitan in Bincau Village, Martapura District, Banjar Regency. The continuance from the training results of this activity is to increase community skills in processing catfish-based products which leads to improvements in the household economic sector through economic growth and increasing incomes of the surrounding community.